Smart Step Ladder - Yusjah, Muhammad Nabil Najmi; Abd Kahar, Hartiny; Amat Rithuan, Muhamad Zulfahizal (Multidisciplinary Applied Research and Innovation, 2021)
In the construction sector, a step ladder is a key construction accessory that is required for contractors or roofers to reach their targets, used as climbing apparatuses to achieve greater heights. The challenges with the traditional step ladder used recently are that it needs to be manually moved around. The operator needs to climb up and down several times to move the ladder to the desired position thus this is time and energy-consuming. The objective of the innovation of the Smart Step Ladder is to facilitate the operator in controlling the movement. Using a mobile application controller to move the ladder around, will save time to complete the tasks since the operator does not have to climb up and down the ladder to change position. This will simultaneously increase the efficiency (faster/easier/safer) and reduce the energy of manpower. The design methodology of this innovation includes metal joining-welding for fabrication of the mechanical and electrical part, while control of the movement of the Smart Step Ladder using a mobile phone is developed using IoT - Arduino. The operator can control the movement of the step ladder using input keypads on the mobile app or voice control. The invention of this innovation provides exposure of IoT application in the design construction tools and the way it creates an environment for effective resource utilization to minimize human effort which ultimately saves time and improves security